2016
DOI: 10.1051/0004-6361/201526267
|View full text |Cite
|
Sign up to set email alerts
|

[C II] 158μm and [N II] 205μm emission from IC 342

Abstract: Context. Atomic fine-structure line emission is a major cooling process in the interstellar medium (ISM). In particular the [C II] 158 µm line is one of the dominant cooling lines in photon-dominated regions (PDRs). However, it is not confined to PDRs but can also originate from the ionized gas closely surrounding young massive stars. observed with the GREAT receiver on board SOFIA.We present different methods to utilize the superior spatial and spectral resolution of our new data to infer information on how … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
1
25
1
Order By: Relevance
“…The finding of a "normal" ratio of 20-40 is therefore surprising and needs to be interpreted carefully. Röllig et al (2016) found a [Cii]/[Nii] luminosity ratio of 12 in the central regions of IC 342, a normal local star-forming galaxy, similar to our own Milky Way, suggesting that a majority of the [Cii] emission originates in ionized gas. However, Lu et al (2015) find a positive correlation between the [Cii]/[Nii] ratio and bluer FIRcolor in local galaxies.…”
Section: Analysis Of the Individual Sourcessupporting
confidence: 71%
“…The finding of a "normal" ratio of 20-40 is therefore surprising and needs to be interpreted carefully. Röllig et al (2016) found a [Cii]/[Nii] luminosity ratio of 12 in the central regions of IC 342, a normal local star-forming galaxy, similar to our own Milky Way, suggesting that a majority of the [Cii] emission originates in ionized gas. However, Lu et al (2015) find a positive correlation between the [Cii]/[Nii] ratio and bluer FIRcolor in local galaxies.…”
Section: Analysis Of the Individual Sourcessupporting
confidence: 71%
“…The c(n e ,T e ) coefficients are scaling factors between I([NII]) and N(N + ) as a function of the adopted n e and T e , that take into account the relative population of the three fine-structure levels of the nitrogen ion ( 3 P 0 , 3 P 1 , and 3 P 2 ) due to collisions with electrons and spontaneous decay. They are calculated for the [NII] 205 µm and 122 µm transitions in Röllig et al (2016). These coefficients are almost constant for 5000 K < T e < 8000 K and vary around 15% for 100 cm −3 < n e < 500 cm −3 (Röllig et al 2016), which are the relevant ranges for the gas physical conditions in the AF region and for the observed [NII] line transition at 205 µm used in this work.…”
Section: [C/n] Elemental Abundance Ratio In the Afmentioning
confidence: 94%
“…Following Röllig et al (2016), under the assumption of local thermodynamic equilibrium (LTE) and optically thin [NII] emission (Goldsmith et al 2015), the ionized nitrogen column density N(N + ) for any given radial velocity component in Table 4 is derived as…”
Section: [C/n] Elemental Abundance Ratio In the Afmentioning
confidence: 99%
“…This variation on 20 ′′ scale is not surprising considering that the 7-pixel footprint of upGREAT covers ∼2.3 pc across, and probably includes a number of different cloud components. Only for the central pixel (pix 1) do both [C ii] (Röllig et al 2016). The rms noise for T mb (K) in the calibrated spectra shown in Figure 5 are in the range of 0.05 to 0.17 K for [N ii], 0.04 to 0.25 K for [C ii] averaged over 7 pixels, and 0.08 to 0.30 K in pixel #1.…”
Section: Observationsmentioning
confidence: 99%
“…Unfortunately the crowding of features along the LOS to the Scutum tangency, as seen in Figures 2 and 5, makes it difficult to correct for the [C ii] absorption using the approach described by Langer et al (2016). The large fraction of [C ii] arising from [N ii] regions is not just a phenomenon in the Galactic plane as Röllig et al (2016) …”
Section: High Density Ionized Gas In the Scutum Molecular Layermentioning
confidence: 99%